Benefits, challenges and opportunities of corporate sustainability - Jacobo-Hernandez Carlos Armando; Jaimes-Valdez Miguel Ángel; Ochoa-Jiménez Sergio (Management, 2021)
The topic of corporate sustainability has gained importance in recent years; unfortunately, confusion persists as to what it represents for businesses and academics. This review of the literature aims to analyse concepts and models related to corporate sustainability and to emphasize the most representative recent findings regarding the benefits, challenges, and opportunities of corporate sustainability. First, a series of benefits are identified, including improved quality, image and reputation for organizations. Second, challenges are recognized, such as the high cost of investment and the lack of consideration of cultural factors, collaboration and innovation. Opportunities are then presented, for example, the implementation of sustainability through life cycle management, the “Eden Project” and analysis of strengths, weaknesses, opportunities and threats (SWOT), among others. Finally, the need to achieve the benefits, take advantage of the opportunities and face the challenges of corporate sustainability in order to balance environmental, social and economic development is highlighted.